An approximation of tribological behavior of Ti1−xAlxN coatings against animal bone in ringer’s solution (2014)
Due to their excellent properties, Ti-Al-N coatings have become attractive for biomedical applications. In this paper, friction and wear properties of Ti1−xAlxN films having various aluminum contents, x, have been studied. Adhesion was measured by the scratch test technique; friction was carried out by a pin-on-disk tribometer using an animal bone-pin as counterpart and Ringer’s solution as simulated body fluid; and wear mechanisms were identified by SEM and EDS. It was found that the coating with x = 0.41 exhibited the highest COF, conserves its integrity as a coating, and causes the lowest wear on the bone in Ringer’s solution